A Wideband Eight-Element Antenna Array With Metal: Frame for 5G New-Radio Applications - Wei Luo; Lefei He; Shanshan Xiao; Gui Liu (International Journal of Antennas and Propagation)
In this paper, the study focuses on metal frame smartphone antennas and presents the implementation of an eight-port broadband MIMO metal frame antenna array for smartphones. The MIMO antenna operates within a wide frequency band ranging from 3.23 to 6.45 GHz, covering the 5G New Radio (NR) band N78 (3.4–3.6 GHz), 5G China band N79 (4.8–5 GHz), and IEEE 802.11ac band (5.15–5.35 GHz and 5.725–5.85 GHz). The novelty of this work lies in the use of dumbbell-shaped defects within a Defected Ground Structure (DGS), which significantly enhances isolation between antenna elements. Each compact antenna element features a stepped radiator and stub, arranged orthogonally at the corners of the array. Through evolutionary design and optimal parameter analysis, we investigate the principles of antenna operation. The results exhibit that the measured isolation between any two antenna elements is superior to 15 dB and the measured reflection coefficients are below −10 dB. The measured overall radiation efficiency of the antenna exceeds 60%, and it is even higher than 75% within the frequency ranges of 3.4–3.6 GHz and 4.8–5 GHz, specifically. Several indicators, such as the envelope correlation coefficient (ECC), diversity gain (DG), total active reflection coefficient (TARC), and mean effective gain (MEG), confirm the antenna’s robust MIMO performance, with strong correlation between simulation and measurement.